Stiffness characteristics of soft finger with embedded SMA fibers. (15th January 2017) - Li, Junfeng; Zu, Lei; Zhong, Guoliang; He, Mingchang; Yin, Haibin; Tan, Yuegang
Abstract: In this paper, a novel variable stiffness finger actuated by heating the embedded SMA fibers is proposed. First, the concept of the variable stiffness mechanism and fabrication of the finger which can demonstrate continuous deformation are presented. Then, the parameters of the SMA used for variable stiffness are identified, which are used to model the phase transformation processes of its Young's modulus. In addition, experimental results show that the bending stiffness of the soft finger can be changed by heating the embedded SMA-3 fibers, resulting in a range of increase 49%. And, the model of the input current for SMA-3 wires and pulling force F 2 used to bend the soft finger is established. At last, the reaction force F 3 of the soft finger's tip for different displacement is discussed with finite element analysis model, which is in qualitative agreement with the experimental results. The maximum range of increase for F 3 is 45.3% when the stiffness changed.